Workshop Pembuatan Asesmen Formatif Pembelajaran Literasi dan Numerasi Transisi PAUD-SD Menyenangkan di Sekolah Dasar: Pengabdian - Noviyanti, Silvina; Budiono, Hendra; Rosyadi, Akhmad Fikri; Zahyuni, Violita; Khoirunnisa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This activity aims to provide teachers with understanding and skills in creating formative assessments for literacy and numeracy learning during the PAUD-SD transition in elementary schools. The activity was implemented using lecture, discussion, question and answer sessions, and guided practice methods to create formative assessments for literacy and numeracy. At the end of the activity, an evaluation was conducted to assess the participants' understanding. The results of this activity showed a high level of participant satisfaction, indicated by a high average score of 90.5%. Based on the results of the workshop on creating formative assessments for literacy and numeracy learning during the enjoyable transition from early childhood education to elementary school, it can be concluded that this activity provides added value and knowledge related to creating formative assessments for literacy and numeracy learning. This community service activity requires follow-up related to direct implementation in grade 1, which is part of the transition from early childhood education to elementary school, so that it provides a direct impact of the training that has been carried out.